COMPLETE UNILATERAL CLEFT LIP SURGERY USING MODIFIED ROTATION-ADVANCEMENT FLAP TO ENHANCE AESTHETIC APPEARANCE IN RSPAL DR. RAMELAN HOSPITAL: A CASE SERIES - Hadikhosuma, Jessica Novia; Wicaksono, Bambang; Dhiparedja, Rionaldo (Jurnal Rekonstruksi dan Estetik, 2024)
Highlights: Complete unilateral cleft lip influences not only the aesthetics of the face but also the functionality of the lip, nose, and upper jaw (maxilla). The surgery aims to establish a symmetrical, functional, and visually appealing contour of the lip, vermilion border, and nasal structure. The modified rotation-advancement flap represents a valuable approach for complete unilateral cleft lip repair surgery.   ABSTRACT Introduction: Unilateral cleft lip is  a common congenital anomaly affecting the upper lip and nose, impacting both aesthetics and function. Advances in surgical techniques have enhanced cleft lip repair, with the rotation-advancement flap being a notable method. This study examines the outcomes of a modified Millard’s rotation-advancement flap technique, developed and refined over 14 years. Case Illustration: Between September 2023 and February 2024, four patients with complete unilateral cleft lip and associated nasal deformity were treated at RSPAL Dr. Ramelan Hospital. Each patient underwent cleft lip repair using the modified rotation-advancement flap technique. Case Illustration: Four patients presented with complete unilateral cleft lip with nose deformity came to RSPAL Dr. Ramelan Hospital between September 2023 and February 2024, We performed cleft lip surgery using the modified rotation-advancement flap for each patient. Discussion: Surgical outcomes showed excellent symmetry, proper vermilion border alignment, and minimal scarring. Complications were rare, with no instances of wound dehiscence or infection. The study discusses the aesthetic and functional improvements achieved with this technique, underscoring its effectiveness in treating complete unilateral cleft lip and enhancing patient quality of life. Conclusion: The Modified Rotation-Advancement Flap technique provides a valuable approach for unilateral cleft lip repair, yielding satisfactory aesthetic and functional results. Further research with long-term follow-up and larger sample sizes is needed to confirm its efficacy and refine the technique.